2009
DOI: 10.1183/09031936.00027909
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training in patients with idiopathic pulmonary arterial hypertension

Abstract: We determined the physiological effects of exercise training on exercise capacity and quadriceps muscle function in patients with idiopathic pulmonary arterial hypertension (iPAH).In total, 19 clinically stable iPAH patients (New York Heart Association II-III) underwent a supervised exercise training programme for the duration of 12 weeks. Maximal capacity, endurance capacity and quadriceps function were assessed at baseline and after 12 weeks. In 12 patients, serial quadriceps muscle biopsies were obtained.6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
204
1
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(231 citation statements)
references
References 33 publications
11
204
1
15
Order By: Relevance
“…However, training studies cannot be performed in a blinded design and a selection bias towards highly motivated patients cannot be excluded [1,4]. Other studies that applied a less intense outpatient training programme in small cohorts of pulmonary arterial hypertension (PAH) patients did reveal a less pronounced [3], or even no significant [2,5], improvement in 6MWD or peak oxygen consumption, but an improvement in exercise endurance [2,5] and muscle capillarisation [2]. The effect of training in patients with other aetiologies of pulmonary hypertension (PH), such as associated PAH (APAH) or outof-proportion PH with left heart failure or respiratory diseases, has not yet been evaluated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, training studies cannot be performed in a blinded design and a selection bias towards highly motivated patients cannot be excluded [1,4]. Other studies that applied a less intense outpatient training programme in small cohorts of pulmonary arterial hypertension (PAH) patients did reveal a less pronounced [3], or even no significant [2,5], improvement in 6MWD or peak oxygen consumption, but an improvement in exercise endurance [2,5] and muscle capillarisation [2]. The effect of training in patients with other aetiologies of pulmonary hypertension (PH), such as associated PAH (APAH) or outof-proportion PH with left heart failure or respiratory diseases, has not yet been evaluated.…”
mentioning
confidence: 99%
“…P revious studies in rather small cohorts of patients with idiopathic pulmonary arterial hypertension (IPAH) and inoperable chronic thromboembolic pulmonary hypertension (CTEPH) have shown beneficial effects of exercise training as add-on to disease-targeted medical therapy, by increasing exercise capacity [1][2][3] and quality of life [1]. Exercise training also improved peak oxygen consumption and World Health Organization (WHO) functional class [1], and possibly the clinical outcome, with 1-and 2-yr survival rates of 100 and 95%, respectively [4].…”
mentioning
confidence: 99%
“…However, increasing data in the literature describe peripheral vascular damage in PAH, suggesting a more systemic impairment in this disease. 74,75 Potus et al 76 showed a decrease of capillary density in peripheral skeletal muscles of PAH patients, suggesting a peripheral angiogenesis defect in PAH. Furthermore, they identified the molecular pathway implicated and showed the major role of microRNA in this pathological process.…”
Section: Systemic Angiogenic Impairment In Pahmentioning
confidence: 99%
“…Despite this reduced ventilatory capacity and increased demand, ventilatory limitation is said not to occur in PAH unless there is concomitant lung disease. Peripheral muscle dysfunction has been shown in PAH in the form of reduced capillary density and oxidative enzymes in muscle biopsies of these patients [10]. This abnormality can lead to impairment of extraction of oxygen from muscle capillaries and should be reflected in abnormally high values of S v O 2 at end-exercise [11].…”
Section: Introductionmentioning
confidence: 99%